2013
DOI: 10.4103/0974-2700.106319
|View full text |Cite
|
Sign up to set email alerts
|

Emergency thoracotomies: Two center study

Abstract: Introduction and Aim:Emergency thoracotomy is performed either immediately at the scene of injury, in the emergency department or in the operating room. It aims to evacuate the pericardial tamponade, control the haemorrhage, to ease the open cardiac massage and to cross-clamp the descending thoracic aorta to redistribute blood flow and maybe to limit sub-diaphragmatic haemorrhage, bleeding and iatrogenic injury are the common risk factors. We aimed to review our experience in the field of emergency thoracotomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…However unexpected survivors from traumatic cardiac arrest are clearly described with good neurological outcomes in both adult and paediatric practice [3,5,11,[25][26][27][28][29]. Indeed in patients with penetrating cardiac wounds survival is now around 7.5-30%, higher than medical cardiac arrest overall and similar to witnessed VT/VF with immediate bystander CPR [3,5,[7][8][9][10]30].…”
Section: Discussionmentioning
confidence: 97%
“…However unexpected survivors from traumatic cardiac arrest are clearly described with good neurological outcomes in both adult and paediatric practice [3,5,11,[25][26][27][28][29]. Indeed in patients with penetrating cardiac wounds survival is now around 7.5-30%, higher than medical cardiac arrest overall and similar to witnessed VT/VF with immediate bystander CPR [3,5,[7][8][9][10]30].…”
Section: Discussionmentioning
confidence: 97%
“…They go on to say that emergency thoracotomy has an important role in emergency big volume hospitals and can save a lot of lives. 11 Our two patients were Cardiac penetration patients and fortunately the grater vessels were missed. We followed the recommend facts of the Advanced Trauma life support (ATLS) guidelines and emergency thoracotomy in penetrating thoracic injuries based on their rules.…”
Section: Discussionmentioning
confidence: 83%
“…We followed the recommend facts of the Advanced Trauma life support (ATLS) guidelines and emergency thoracotomy in penetrating thoracic injuries based on their rules. 11 One typical reason is what Ordog GJ et al 12 found out: Of the four among their patients with initially unsuspected cardiac injuries, two patients died in the operating room. These were Asymptomatic patients with normal findings on chest x-ray films.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations